2019
DOI: 10.1097/qai.0000000000001881
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Relates to Poorer Complex Motor Performance Among Adults Living With HIV on Suppressive Antiretroviral Therapy

Abstract: Background: Inflammatory processes have been suggested to underlie early neurologic abnormalities among persons living with HIV (HIV-positive), such as deficits in complex motor function, that are purported to remit with effective antiretroviral treatment (ART). We hypothesized HIV will have negative direct and indirect effects via inflammation on complex motor performance. Methods: The sample consisted of 90 ART-treated virally suppressed HIV-positive and 94 HIV-negative adults, ages 36 to 65 years, with ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 51 publications
4
16
0
Order By: Relevance
“…This cross-level interaction between study-average depressive symptoms and visitspecific inflammation on global neurocognition was driven by statistically significant interactions in the domains of processing speed, fine motor skills, and attention/working memory. We previously detected acute deleterious effects of depressive symptoms on processing speed and motor skills in a separate sample of PWH (Paolillo et al 2020a), andMontoya et al (2019) found that higher peripheral inflammation mediated the adverse effect of HIV on motor skills (Montoya et al 2019). In HIV-seronegative patients with MDD, higher plasma CRP has been related to elevated extrasynaptic glutamate in the basal ganglia as measured by magnetic resonance spectroscopy, which in turn related to anhedonia and slower performance on psychomotor tests (Haroon et al 2016).…”
Section: Discussionmentioning
confidence: 98%
“…This cross-level interaction between study-average depressive symptoms and visitspecific inflammation on global neurocognition was driven by statistically significant interactions in the domains of processing speed, fine motor skills, and attention/working memory. We previously detected acute deleterious effects of depressive symptoms on processing speed and motor skills in a separate sample of PWH (Paolillo et al 2020a), andMontoya et al (2019) found that higher peripheral inflammation mediated the adverse effect of HIV on motor skills (Montoya et al 2019). In HIV-seronegative patients with MDD, higher plasma CRP has been related to elevated extrasynaptic glutamate in the basal ganglia as measured by magnetic resonance spectroscopy, which in turn related to anhedonia and slower performance on psychomotor tests (Haroon et al 2016).…”
Section: Discussionmentioning
confidence: 98%
“…This likely reflects the fact that the prevalence of HAD and extrapyramidal motor signs in HIV has decreased (Smail & Brew, 2018) and the disease course altered by ART, resulting in less severe neurocognitive impairment earlier during the course of HIV infection (Heaton et al ., 2010; Heaton et al ., 2011; Sacktor et al ., 2001; Simioni et al ., 2010; but see Gisslen et al ., 2011). Here, 14% of our older HIV participants showed at least mild motor impairment, suggesting that motor symptoms remain a functional consequence of HIV infection (Dehner et al ., 2016; Montoya et al ., 2019) with older age (Valcour et al ., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, compared to healthy controls, PLWH on long-term cART had higher levels of CST5, 4E-BP1, SLAMF1, CCL23, MMP1, ADA, and CD8A and lower levels of NT3, TRAIL, and sCD5 in plasma ( 42 ). Additionally, peripheral inflammatory cytokines (d-dimer, IL-6, MCP-1/CCL2, sCD14, and TNF-α) in HIV-infection have been correlated with impaired complex motor performance, though not a HAND-specific biomarker ( 108 ). Furthermore, it has been suggested that these proteins are associated with early stages of age-related diseases ( Table 1 ).…”
Section: Cytokines Chemokines and Inflammagingmentioning
confidence: 99%